Faktor kegemilangan tamadun Islam : pengajaran dari masa lalu - Khalif Muammar (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
This article is an attempt to analyse the factors behind the rise and fall of Islamic civilisation. The author contends that looking at the achievement of Muslims in the past is inadequate. Hence, the article underlines the civilisational foundations laid down since the Prophet’s era. It stresses the holistic development of human being, the strengthening of Islamic identity through the concept of Tawhid, the culture of knowledge, and aspects of morality and social solidarity (‘asabiyyah). The author also relates the decline of Islamic civilization with the corruption in these foundations such as epistemological confusion, the loss of knowledge culture and social solidarity, the loss of adab or morality and the despotic nature of Muslim leadership.